AN EARLY PERMIAN GARNET-BEATING PERALUMINOUS GRANITIC PLUTON IN THE SOUTH TIANSHAN OROGENIC BELT, NW CHINA: PETROLOGICAL, MINERALOGICAL AND GEOCHEMICAL CONSTRAINTS - Qie Qin; He Huang; Tao Wang; Zhaochong Zhang (Геодинамика и тектонофизика, 2017)
The Ku’erchu granitic pluton (283±4 Ma) was exposed in the eastern part of the South Tianshan Orogenic Belt. The granites from the intrusion are mainly composed of orthoclase (~45 vol. %), plagioclase (~15 vol. %), quartz (~20 vol. %), muscovite (~10 vol. %) and biotite (~5 vol. %), with accessory minerals including garnet, zircon and Fe-Ti oxide.